Biomechanical testing of distal femur osteotomy plate fixation techniques: the role of simulated physiological loading - Justus‐Martijn Brinkman; Christof Hurschler; Jens Agneskirchner; Philip Lobenhoffer; René M Castelein; Ronald J vanHeerwaarden (Journal of Experimental Orthopaedics, 2014)
Abstract Background Implants for fracture and/or osteotomy fixation are often tested according to basic mechanical test models such as open gap tests or 4‐point‐bending tests. These may be suitable to test and compare different implants for safety and clinical approval, but are not always representative of the post‐operative situation, which is decisive when it comes to bone healing. In the current study the Knee Expert Group of the Association for the Study of Internal Fixation has compared the available open gap test results of the latest version of the TomoFix Medial Distal Femoral Plate and the antecedent plate design, with the test results of a more physiological and life‐like test model. In the open gap test model the antecedent plate design was found to have superior stiffness and fatigue strength. Methods In the current study simulated postoperative conditions for medial closing wedge supracondylar osteotomies were used. The constructs were subjected to cyclical axial and torsional loading and were subsequently tested to failure. Results The more life‐like tests in this study showed that the latest version was either more or equally stable and stiff than the antecedent version of the plate, in all of the tests. It is argued that the difference in results between the two loading models is due to differences in test design. Conclusions These test results stress the importance of not only using standard open gap and 4‐point‐bending tests, but also to use as life‐like as possible test conditions for any form of biomechanical testing of new implants.